(untitled) (American Journal of Islam and Society, 2014)
Although I did not study under Isma’il al-Faruqi (d. 1986) directly as did scholars like John Esposito and many others, I have, nonetheless, had the pleasure of teaching and introducing my students to his person and ideas for the past decade. His former students have convened two conferences (London [2010] and Kuala Lumpur [2013]) to celebrate his intellectual contribution, from which came a book and a special issue of this journal. Could all of this be sentimental hero worship, or a life worthy of sincere celebration and emulation? Studying his intellectual publications and tracing his academic and social activities make it abundantly clear that he was unique and committed to improving the lot of Islam and Muslims. John Esposito and John Voll narrate in their Makers of Contemporary Islam a brief story: “An old Christian acquaintance of al-Faruqi once commented that al-Faruqi believed that Islam was in need of reformation and, he believed, al-Faruqi aspired to be its Luther.”1 Even though this was a sincere assessment, Esposito and Voll speculate that al-Faruqi would have preferred the word mujāhid. Esposito prefers to use this term to describe al-Faruqi, as he did in his “Memoirs of a Scholar and a Mujahid.”2 Although al-Faruqi never referred to himself in this way, portraying him as Islam’s Martin Luther does have some significance to contemporary Islam and Islamic thought. Luther appeared on the Christian intellectual and religious scene during the 1500s, a time when Christian theology and thought were perceived as profoundly corrupt. There were indulgences, essentially “get out of purgatory free” cards, that only the rich and powerful could afford. Championed by popes and princes, this practice undermined the Christian’s role of personal responsibility and Jesus’ message (peace be upon him). Church leaders sought to monopolize religious knowledge by prohibiting translations of the Bible and to stifle the pursuit of knowledge by publishing their Index of Forbidden Books (from 1559 to 1966, when Pope Paul VI abolished it). The church hierarchy also began teaching that following the Bible ...